Hydrogel preparation method based on nano lignin
By preparing a combination of nano-lignin particles and silver nanoparticles to form a dense porous network hydrogel, the problem of insufficient mechanical properties of PVA-based hydrogels was solved, and high strength, toughness and pressure sensitivity were achieved, making it suitable for flexible sensors and biomedical devices.
Patent Information
- Application Number
- CN202510901091.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2025-09-30
AI Technical Summary
The mechanical properties of existing PVA-based hydrogels are generally insufficient, with low tensile strength and low elongation at break, which makes it difficult to meet the high-strength and toughness material requirements of flexible sensors and biomedical devices. Traditional methods of improving mechanical properties often lead to poor compatibility and stress attenuation.
Nano-lignin particles were prepared by pretreating lignin-rich cellulose biomass raw materials with choline chloride-lactic acid deep eutectic solvent, and then reacted with silver nitrate and sodium hydroxide to synthesize lignin-silver nanoparticles. After adding polyvinyl alcohol solution, nano-composite hydrogels were formed through freeze-thaw cycles, avoiding chemical cross-linkers and forming a dense porous network.
The tensile strength of the hydrogel was increased to 0.7-0.9 MPa, the elongation at break was 280-320%, the Young's modulus was 2.0-2.5 kPa, the compressive stress was 200-250 kPa, the pressure sensitivity was 2.5-2.7 kPa-1, and the cyclic compressive stress was reduced by less than 3%, making it suitable for flexible sensors and biomedical devices.
Smart Images

Figure CN120718299A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomaterials and nanotechnology, and in particular to a method for preparing a hydrogel based on nano-lignin. Background Art
[0002] Hydrogels are widely used in flexible sensors, biomedical devices and sustainable materials due to their high water content, flexibility and biocompatibility. Polyvinyl alcohol (PVA), as a common hydrogel matrix, is often used to prepare composite hydrogels due to its good film-forming and solubility. In recent years, lignin, as a renewable biomass resource, has attracted attention due to its rich functional groups and low cost. Lignin can be converted into low molecular weight nanoparticles (LNPs) through deep eutectic solvent (DES) pretreatment and reacted with metal ions (such as Ag). + ) to form functional nanocomposites. Prior art methods for combining PVA with LNPs or metal nanoparticles have been reported, such as preparing hydrogels with electrical conductivity and antibacterial properties through chemical crosslinking or physical mixing. Some studies have used freeze-thaw processes to achieve physical crosslinking to enhance the mechanical properties and functionality of the material.
[0003] However, the mechanical properties of existing PVA-based hydrogels are generally insufficient, with tensile strengths typically ranging from 0.1-0.2 MPa, elongation at break less than 200%, and compressive stresses of only 30-50 kPa at 60% strain, making them difficult to meet the high-strength and toughness requirements of flexible sensors and biomedical devices. Traditional methods enhance mechanical properties by adding chemical crosslinkers or high-molecular-weight lignin, but this often results in poor compatibility, uneven dispersion, limited improvement in mechanical properties, and a tendency to experience stress decay (>10%) after cyclic compression. Summary of the Invention
[0004] In view of the shortcomings of the existing technology, the present invention provides a method for preparing a hydrogel based on nano-lignin, which solves the problem that the mechanical properties of existing PVA-based hydrogels are generally insufficient.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing a hydrogel based on nano-lignin, comprising the following steps:
[0006] S1. Pretreating a cellulose biomass raw material containing more than 15% lignin using a choline chloride-lactic acid deep eutectic solvent to prepare nano-lignin particles;
[0007] S2, mixing the nano-lignin particles with silver nitrate and sodium hydroxide to synthesize lignin-silver nanoparticles through redox reaction;
[0008] S3, adding the lignin-silver nanoparticles to the polyvinyl alcohol solution and mixing to form a mixture;
[0009] S4. The mixture is subjected to freeze-thaw cycles to induce physical cross-linking to form a nanocomposite hydrogel.
[0010] According to the above technical solution, step S1 selects cellulose biomass raw materials with >15% lignin as raw materials, pre-treats them with choline chloride-lactic acid deep eutectic solvent (1:2 molar ratio) to break the chemical bonds of lignin and reduce the molecular weight, and then forms nano-lignin particles by ultrasonic dispersion. Step S2 reacts the nano-lignin particles with silver nitrate and sodium hydroxide to reduce the phenolic hydroxyl and methoxy groups of lignin to Ag. + Silver nanoparticles are used to form lignin-silver nanoparticles. Step S3 prepares an 8-12% polyvinyl alcohol solution (molecular weight 80,000-100,000 g / mol), adds lignin-silver nanoparticles, and stirs to form a mixture. Step S4 pours the mixture into a mold and forms a hydrogel through 2-4 freeze-thaw cycles (-25 to -15°C, 4-8 hours; 20-30°C, 1-3 hours). This method does not require chemical crosslinking agents, has a simple process, and is suitable for the fields of sensors, biomedicine, and sustainable materials.
[0011] Preferably, in step S1, the choline chloride-lactic acid deep eutectic solvent pretreatment is carried out at 100-140° C. for 4-8 hours, and the obtained nano-lignin particles have a weight average molecular weight of 1400-1700 g / mol and a polydispersity coefficient of 1.2-1.5.
[0012] Preferably, in step S2, the nano-lignin particles are dissolved in a sodium hydroxide solution with a pH of 9-11 at a concentration of 0.04-0.06 g·mL -1 , silver nitrate concentration is 0.08-0.12 g·mL -1 The obtained lignin-silver nanoparticles had a particle size of 300-350 nm and a zeta potential of -25 to -35 mV.
[0013] Preferably, in step S3, the mass fraction of the polyvinyl alcohol solution is 8-12%, and the solution is prepared at 70-90°C. After the lignin-silver nanoparticles are added, the solution is stirred at 60-70°C for 0.5-1.5 hours. + The mass fraction is 15% to 25%.
[0014] Preferably, in step S4, the freeze-thaw cycle is 2-4 times, the freezing condition is -25 to -15°C for 4-8 hours, the thawing condition is 20-30°C for 1-3 hours, and the mold specification is 90-110mm×90-110mm×8-12mm.
[0015] Preferably, a nano-lignin-based hydrogel is based on polyvinyl alcohol and contains lignin-silver nanoparticles, Ag + The mass fraction is 15% to 25%, and the specific surface area is 1.2-1.4m 2 ·g -1 , with a uniform porous network structure.
[0016] Preferably, when Ag + When the mass fraction is 20%, the tensile strength is 0.7-0.9MPa, the elongation at break is 280-320%, the Young's modulus is 2.0-2.5kPa, and the toughness is 1.0-1.3MJ·m -3 .
[0017] Preferably, the compressive stress at 60% strain is 200-250 kPa, and there is no significant stress reduction after 80-120 compression cycles at 40% strain.
[0018] Preferably, the pressure sensitivity is 2.5-2.7 kPa -1 , the storage modulus and loss modulus are 8–12 times higher than those of pure PVA hydrogel in the frequency range of 0.01 to 10 Hz, exhibiting shear-thinning behavior.
[0019] Preferably, it is applied to flexible sensors, biomedical devices or sustainable materials, and is suitable for wearable electronic devices, wound dressings, tissue engineering, construction or furniture.
[0020] The present invention provides a method for preparing a hydrogel based on nano-lignin. It has the following beneficial effects:
[0021] 1. The present invention combines DES pretreated nano-lignin particles with silver ions and embeds them into a PVA matrix to form a dense porous network, so that the hydrogel not only has good mechanical properties (tensile strength reaches 0.7-0.9MPa), but also has good toughness and ductility (1.0-1.3MJ·m -3 ), excellent pressure sensitivity (pressure sensitivity is 2.5-2.7kPa -1 ), compressive stress 200-250kPa (6-8 times that of pure PVA), hydrogen bonding and uniform dispersion of Lig-AgNPs enhance energy dissipation, and the stress reduction of cyclic compression (40% strain, 80-120 times) is less than 3%, providing high-strength and tough materials for flexible sensors and biomedical devices.
[0022] 2. The present invention introduces Lig-AgNPs to obtain a hydrogel with a viscosity of 2.5-2.7 kPa -1The pressure sensitivity is 2.5-3 times that of pure PVA, the relative resistance change responds linearly in the range of 0-100kPa, and the resistance recovery rate after cyclic loading (20% and 40% strain, 50 times) is over 95%. AgNPs form a conductive network, and the distance between particles decreases during compression, enhancing electron transfer. UV-visible spectroscopy confirms the presence of AgNPs, making the hydrogel suitable for strain and pressure sensors.
[0023] 3. The present invention adopts a one-pot process and freeze-thaw cycles (2-4 times, -25 to -15 ° C, 4-8 hours), without the need for chemical cross-linking agents, reducing process complexity and environmental pollution. Renewable lignin and DES pretreatment are used, waste liquid can be recycled, and the specific surface area reaches 1.2-1.4m 2 ·g -1 The process is simple, suitable for large-scale production, and provides support for sustainable material development.
[0024] 4. The present invention uses DES pretreatment to produce nano-lignin particles with a molecular weight of 1400-1700 g / mol, a zeta potential of -25 to -35 mV, a particle size of 300-350 nm, and a particle size change of less than 5% after 30 days of storage. Lig-AgNPs are hydrogen-bonded with PVA, and SEM analysis shows uniform dispersion with pore sizes of 10-50 μm, improving compatibility and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 SEM images of Lig-AgNPs and Lig-FeNPs of the present invention;
[0026] Figure 2 Schematic diagram of the nanoparticle size of Lig-AgNPs of the present invention;
[0027] Figure 3 FTIR graph of Lig-AgNPs of the present invention;
[0028] Figure 4 is the UV image of DES-Lig-AgNPs of the present invention;
[0029] Figure 5 Schematic diagram of the preparation mechanism of the hydrogel of the present invention;
[0030] Figure 6 Schematic diagram of the tensile strength and Young's modulus of the hydrogel of the present invention;
[0031] Figure 7 Schematic diagram of the compression curve of the PVA / Lig-Ag hydrogel of the present invention subjected to 100 consecutive loading-unloading cycles at 40% strain;
[0032] Figure 8Schematic diagram of the changes in the storage modulus (G') and loss modulus (G") of the hydrogel of the present invention at different frequencies;
[0033] Figure 9 Schematic diagram of the viscosity change of the hydrogel at different shear rates of the present invention;
[0034] Figure 10 Schematic diagram of the relative resistance change of the hydrogel of the present invention under different pressures. DETAILED DESCRIPTION
[0035] The following will clearly and completely describe the technical solution of the present invention in conjunction with the accompanying drawings. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0036] Please see the attached Figure 1 -Attached Figure 10 The present invention provides a method for preparing a hydrogel based on nano-lignin, comprising the following steps:
[0037] S1. Pretreating a cellulose biomass raw material containing more than 15% lignin using a choline chloride-lactic acid deep eutectic solvent to prepare nano-lignin particles;
[0038] S2, mixing the nano-lignin particles with silver nitrate and sodium hydroxide to synthesize lignin-silver nanoparticles through redox reaction;
[0039] S3, adding the lignin-silver nanoparticles to the polyvinyl alcohol solution and mixing to form a mixture;
[0040] S4. The mixture is subjected to freeze-thaw cycles to induce physical cross-linking to form a nanocomposite hydrogel.
[0041] Specifically, in step S1, a cellulose biomass raw material with >15% lignin is selected as the raw material because it is rich in lignin, widely available, and low in cost. Choline chloride-lactic acid deep eutectic solvent (DES) is prepared in a 1:2 molar ratio and formed into a uniform transparent liquid by heating and stirring, which is used to destroy the complex chemical bonds of lignin, reduce the molecular weight and increase the reaction activity. After pretreatment, the lignin is filtered, washed and dried to obtain purified DES lignin, which is then dispersed by ultrasound to form nanoparticles. Step S2 converts silver ions (Ag) into lignin by redox reaction. + ) is reduced to silver nanoparticles (AgNPs) by using the phenolic hydroxyl and methoxy groups of lignin as reducing agents, avoiding the use of additional chemical reagents. The addition of sodium hydroxide forms [Ag(NH3)2] +Complex, stabilize the reaction system and improve the uniformity of silver nanoparticles. In step S3, polyvinyl alcohol (PVA) solution is prepared by high-temperature dissolution. PVA uses industrial-grade products with a molecular weight of 80,000-100,000 g / mol to ensure good film-forming properties and mechanical properties. Lignin-silver nanoparticles (Lig-AgNPs) are added to the PVA solution by slow dropwise addition to avoid agglomeration caused by excessive local concentration. The mixing process is carried out in a constant temperature water bath, and the stirring speed is controlled at 200-300 rpm to ensure uniform dispersion. The freeze-thaw cycle of step S4 forms a hydrogel network through physical cross-linking. The freezing process partially crystallizes the PVA chain, and the thawing process promotes the formation of hydrogen bonds. The addition of Lig-AgNPs enhances the density and toughness of the network. The mold is made of polytetrafluoroethylene material, and the size is precisely controlled to ensure the consistency of the hydrogel morphology. This method does not require a chemical cross-linking agent, the process is green and environmentally friendly, and is suitable for large-scale production. The resulting hydrogel has broad application prospects in the fields of flexible sensors, biomedicine and building materials.
[0042] In step S1, the choline chloride-lactic acid deep eutectic solvent pretreatment is carried out at 100-140° C. for 4-8 hours, and the obtained nano-lignin particles have a weight average molecular weight of 1400-1700 g / mol and a polydispersity coefficient of 1.2-1.5.
[0043] Specifically, in step S1, the pretreatment process of the choline chloride-lactic acid deep eutectic solvent is optimized to ensure that the molecular weight and dispersibility of the nano-lignin particles (DES-Lig-NPs) reach the ideal range. Choline chloride and lactic acid are mixed in a 1:2 molar ratio, stirred at 80°C until a transparent liquid is formed, and then cooled to room temperature for use. 15% of the lignin-rich cellulosic biomass raw material is mechanically crushed to 40-60 mesh, added to DES, and the solid-liquid ratio is 1:10 (g / mL). It is stirred in an oil bath at 100-140°C for 4-8 hours at a stirring speed of 150-200 rpm. During the pretreatment process, DES breaks the ester bonds, carbon-carbon bonds and β-O-4 ether bonds in lignin through hydrogen bonding and solvation, resulting in a significant reduction in molecular weight. After the reaction is completed, the mixture is separated by suction filtration, and the residue is washed 3-5 times with deionized water to remove DES residues and soluble impurities. The obtained lignin was vacuum dried at 60 °C for 12 h and then dissolved in a NaOH solution with a pH of 9-11 (concentration of 0.04-0.06 g mL -1) and treated with an ultrasonic processor (power 200-300W, frequency 20kHz) for 20-40 minutes to obtain uniformly dispersed DES-Lig-NPs. Molecular weight was determined by gel permeation chromatography (GPC) using tetrahydrofuran as the mobile phase and polystyrene as the standard sample. The results showed a weight-average molecular weight (Mw) of 1400-1700 g / mol and a polydispersity index (PDI) of 1.2-1.5, indicating a uniform molecular weight distribution and high reactivity. The low molecular weight and uniformity of DES-Lig-NPs provide good compatibility with the PVA matrix, laying the foundation for subsequent silver nanoparticle synthesis and hydrogel preparation.
[0044] In step S2, the nano-lignin particles are dissolved in a sodium hydroxide solution with a pH of 9-11 at a concentration of 0.04-0.06 g·mL -1 , silver nitrate concentration is 0.08-0.12 g·mL -1 The obtained lignin-silver nanoparticles had a particle size of 300-350 nm and a zeta potential of -25 to -35 mV.
[0045] Specifically, the synthesis process of lignin-silver nanoparticles (Lig-AgNPs) in step S2 achieves the particle size and stability of nanoparticles by precisely controlling the reaction conditions. Nano-lignin particles (DES-Lig-NPs) are dissolved in a NaOH solution with a pH of 9-11 at a concentration of 0.04-0.06 g·mL -1 , stir at 25°C for 30 minutes using a magnetic stirrer (300-400 rpm) to ensure complete dissolution. Then, slowly add silver nitrate (AgNO3, analytical grade) to a concentration of 0.08-0.12 g mL -1 , stir for 10 minutes to make Ag + Then, add 28% sodium hydroxide (NH3·H2O) dropwise until the solution becomes clear, forming [Ag(NH3)2] + The reaction system was stirred continuously at 25-30℃ for 1-2 hours to promote the reaction of phenolic hydroxyl (-OH) and methoxy (-OCH3) of lignin with Ag. + The functional groups of lignin are oxidized to quinone / semiquinone radicals, Ag +It is reduced to AgNPs and attached to the surface of lignin. After the reaction is completed, the solution is brown, indicating that Lig-AgNPs are formed. The particle size is 300-350nm and the zeta potential is -25 to -35mV by dynamic light scattering (DLS), indicating that the particles have high stability and are suitable for long-term storage. Scanning electron microscopy (SEM) shows that Lig-AgNPs have a regular ring morphology and uniform internal pores, indicating that AgNPs are tightly bound to lignin. Fourier transform infrared spectroscopy (FT-IR) analysis further confirmed that the 1608cm -1 (aromatic ring), 1272cm -1 (phenolic hydroxyl) and 1033cm -1 The peak intensity at (methoxy) decreases, proving that Ag + The oxidation of lignin functional groups was induced. Ultraviolet-visible spectroscopy (UV-Vis) showed a surface plasmon resonance peak at 417 nm, confirming the presence of AgNPs.
[0046] In step S3, the mass fraction of the polyvinyl alcohol solution is 8-12%, and it is prepared at 70-90°C. After the lignin-silver nanoparticles are added, the mixture is stirred at 60-70°C for 0.5-1.5 hours. + The mass fraction is 15% to 25%.
[0047] Specifically, in step S3, the preparation of polyvinyl alcohol (PVA) solution and the integration process of lignin-silver nanoparticles (Lig-AgNPs) are optimized to ensure the uniformity of the mixture and the performance of the hydrogel. PVA is an industrial-grade product with a degree of alcoholysis of 98-99% and a molecular weight of 80,000-100,000 g / mol, dissolved in deionized water with a mass fraction of 8-12%. PVA powder is slowly added to deionized water at 70-90°C, with a stirring speed of 200-300 rpm and continuous stirring for 2-3 hours until a transparent and uniform solution is formed. After the solution is cooled to 60-70°C, a burette is used to add the Lig-AgNPs solution (concentration 0.04-0.06 g·mL) at a rate of 1-2 mL / min. -1 ) was added dropwise to the PVA solution with a total volume ratio of 1:1 to 1:2. During the addition, the stirring speed was maintained at 250-350 rpm and the stirring time was 0.5-1.5 hours to ensure that the Lig-AgNPs were evenly dispersed and agglomeration was avoided. +The mass fraction of the Lig-AgNPs solution was controlled between 15% and 25% by adjusting the addition amount, corresponding to the PVA / Lig-Ag-15, PVA / Lig-Ag-20, and PVA / Lig-Ag-25 hydrogels, respectively. The mixture was uniformly brown with no noticeable precipitation, indicating good compatibility between the Lig-AgNPs and the PVA matrix. To verify homogeneity, samples were taken for optical microscopy, confirming the absence of micron-sized aggregates. During the mixing process, the hydroxyl groups on the PVA chains interacted with the functional groups on the surface of the Lig-AgNPs through hydrogen bonding, initially forming a physical cross-linked network that provided the foundation for the subsequent freeze-thaw process. The optimized process conditions ensured the hydrogels exhibited excellent mechanical properties, electrical conductivity, and pressure sensitivity.
[0048] In step S4, the freeze-thaw cycle is 2-4 times, the freezing condition is -25 to -15°C for 4-8 hours, the thawing condition is 20-30°C for 1-3 hours, and the mold specification is 90-110mm×90-110mm×8-12mm.
[0049] Specifically, the freeze-thaw cycle process in step S4 forms a stable nanocomposite hydrogel network through physical cross-linking, and the mold design and cycle conditions are optimized to ensure the consistency of the morphology and performance of the hydrogel. The mixture (PVA and Lig-AgNPs) is poured into a polytetrafluoroethylene mold with a mold size of 90-110mm×90-110mm×8-12mm and a smooth inner surface for easy demolding. The mold is placed in a freezer at -25 to -15°C and frozen for 4-8 hours to partially crystallize the PVA chains and form microcrystalline regions. Subsequently, the mold is transferred to a constant temperature box at 20-30°C and thawed for 1-3 hours to promote the formation of hydrogen bonds between the PVA chains and Lig-AgNPs. The freeze-thaw cycle is repeated 2-4 times. Experiments show that 3 cycles can obtain the best mechanical properties. Too many cycles may cause the structure to be too dense and reduce toughness. During the freezing process, the hydrophobic interaction of Lig-AgNPs induces nanophase separation, forming a uniform porous network with a specific surface area of 1.2-1.4m 2 ·g -1 (Determined by BET method). During the thawing process, NH3 bubbles (derived from sodium hydroxide during the synthesis of Lig-AgNPs) partially escaped, forming micropores in the hydrogel, further enhancing the porosity. The resulting hydrogel was a brown translucent cube with a smooth surface and no obvious defects. SEM analysis showed that the hydrogel had a dense and uniform porous structure with a pore size distribution of 10-50μm, which is conducive to mechanical strength and electrolyte ion transport. The freeze-thaw process does not require chemical cross-linking agents, is green and environmentally friendly, and the range design of mold size and cycle conditions makes it suitable for production needs of different scales.
[0050] A nano-lignin-based hydrogel with polyvinyl alcohol as the matrix and containing lignin-silver nanoparticles, Ag + The mass fraction is 15% to 25%, and the specific surface area is 1.2-1.4m 2 ·g -1 , with a uniform porous network structure.
[0051] Specifically, polyvinyl alcohol (PVA) is used as the matrix, and lignin-silver nanoparticles (Lig-AgNPs) are embedded. + The mass fraction is 15% to 25%, forming a functional material with excellent mechanical properties, conductivity and pressure sensitivity. The PVA matrix provides flexibility and biocompatibility, and the Lig-AgNPs enhance the network structure through hydrogen bonding and nanophase separation. The specific surface area is determined by the BET method to be 1.2-1.4 m 2 ·g -1 , higher than pure PVA hydrogel (1.0-1.2m 2 ·g -1 ), attributed to the nanopores induced by Lig-AgNPs and the pore-forming effect of NH3 bubbles. SEM observations showed that the hydrogel had a uniform porous network with a pore size of 10-50μm, a pore wall thickness of 5-10μm, and a regular pore distribution, which enhanced the mechanical strength and ion transport efficiency. The chemical composition of the hydrogel was analyzed by X-ray photoelectron spectroscopy (XPS), confirming that AgNPs were in the form of zero-valent silver (Ag 0 ) form, indicating that the redox reaction is complete. Infrared spectroscopy (FT-IR) shows that the hydroxyl peak of PVA (3400cm -1 ) and the aromatic ring peak of lignin (1608cm -1 ) strength, demonstrating a tight hydrogen-bonding bond between the two. The hydrogel's zeta potential ranged from -25 to -35 mV, indicating high dispersion stability. After 30 days of storage, there was no significant change in particle size or potential. Performance testing demonstrated that the hydrogel performed well in tensile, compression, and rheological tests, making it suitable for flexible sensors and biomedical devices. Its green preparation process and use of renewable lignin give it significant advantages in the field of sustainable materials.
[0052] When Ag + When the mass fraction is 20%, the tensile strength is 0.7-0.9MPa, the elongation at break is 280-320%, the Young's modulus is 2.0-2.5kPa, and the toughness is 1.0-1.3MJ·m -3 .
[0053] Specifically, when Ag +When the mass fraction is 20%, the obtained PVA / Lig-Ag-20 hydrogel exhibits the best mechanical properties, and the tensile test is carried out using a universal material testing machine (loading rate 5mm / min, sample size 50mm×10mm×2mm). The tensile strength is 0.7-0.9MPa, which is much higher than the 0.1-0.15MPa of pure PVA, and the elongation at break is 280-320%, indicating excellent ductility. The Young's modulus is 2.0-2.5kPa, which is about 5-7 times that of pure PVA, proving that the hydrogel has a high resistance to deformation. The toughness is calculated by the integration of the stress-strain curve and reaches 1.0-1.3MJ·m -3 , which is 6-8 times that of pure PVA. These properties are attributed to the dense physical cross-linked network formed by Lig-AgNPs and PVA, and the uniform porous structure induced by NH3 bubbles. Hydrogen bonds and silver ion interactions act as sacrificial bonds, dissipating energy during stretching and improving toughness. SEM analysis shows that the pores of PVA / Lig-Ag-20 are more uniform than those of pure PVA, and the pore size distribution is narrower (20-40μm). Tensile fracture observations show that the fracture surface has fibrous tensile characteristics, indicating that Lig-AgNPs effectively enhance the slip and energy dissipation of PVA chains. Cyclic tensile tests (10 times, 100% strain) showed that the stress reduction was less than 5%, demonstrating excellent self-recovery ability. The mechanical properties of the hydrogel make it suitable for use in fields such as flexible sensors and tissue engineering scaffolds.
[0054] The compressive stress at 60% strain is 200-250 kPa, and there is no obvious stress reduction after 80-120 compression cycles at 40% strain.
[0055] Specifically, the compressive properties of PVA / Lig-Ag-20 hydrogel were tested by a universal material testing machine (loading rate 2mm / min, sample size 20mm×20mm×10mm). The compressive stress was 200-250kPa at 60% strain, which is about 6-8 times that of pure PVA (30-40kPa). The compressive stress-strain curve shows obvious nonlinear behavior, and energy dissipation is significant under high strain. Continuous compression cycle tests were performed 80-120 times at 40% strain, with a loading-unloading rate of 2mm / min and an interval of 1 second between each cycle. The results showed that the stress reduction was less than 3%, indicating that the hydrogel has excellent fatigue resistance and self-recovery ability. The hysteresis loop area (representing dissipated energy) is 0.5-0.7MJ·m at 40% strain. -3, 5-6 times higher than pure PVA, proving that Lig-AgNPs enhance the energy dissipation capacity of the dynamic cross-linked network. Microstructural analysis shows that the uniform dispersion of Lig-AgNPs and the physical cross-linking of PVA chains form a multi-level network structure, which dissipates energy through hydrogen bond breaking and reorganization during compression. X-ray diffraction (XRD) analysis shows that the crystallinity of PVA / Lig-Ag-20 is 25-30%, which is higher than the 20-25% of pure PVA, indicating that Lig-AgNPs promote the orderly arrangement of PVA chains. The improvement in compression performance makes it suitable for high-load scenarios such as pressure sensors and soft robotic components.
[0056] Pressure sensitivity is 2.5-2.7kPa -1 , the storage modulus and loss modulus are 8–12 times higher than those of pure PVA hydrogel in the frequency range of 0.01 to 10 Hz, exhibiting shear-thinning behavior.
[0057] Specifically, the pressure sensitivity and rheological properties of the PVA / Lig-Ag-20 hydrogel were analyzed by conductivity testing and rheometer analysis. Pressure sensitivity was quantified by the relative resistance change (ΔR / R0). The test setup consisted of a hydrogel sample (20mm×20mm×2mm) held by electrodes and a digital multimeter. When a pressure of 0-100kPa was applied, ΔR / R0 increased linearly with increasing pressure, with a sensitivity of 2.5-2.7kPa. -1 , than pure PVA (0.9-1.0kPa -1 ) is 2.5-3 times higher. Cyclic loading tests (20% and 40% strain, 50 cycles) showed that the resistance change recovered to more than 95% of the initial value, demonstrating stable sensing performance. The conductivity is attributed to the conductive network formed by Lig-AgNPs, and the reduced interparticle spacing during compression enhances electron transfer. Rheological tests used a rotational rheometer (parallel plate diameter 25 mm, gap 1 mm) to perform dynamic frequency sweeps in the frequency range of 0.01-10 Hz. The storage modulus (G') and loss modulus (G") are 8-12 times that of pure PVA. In the low-frequency region, G' is lower than G", and in the high-frequency region, G' exceeds G", indicating that the elasticity of the dynamic hydrogen bond network is enhanced. Shear thinning test (shear rate 0.1-100s -1 ) showed that the viscosity decreased with shear rate, with the initial viscosity of PVA / Lig-Ag-20 ranging from 1000-1500 Pa·s, 3-5 times higher than that of pure PVA. This improvement in rheological properties is attributed to the strong interaction between Lig-AgNPs and PVA, making the hydrogel suitable for applications requiring high-sensitivity sensors and high processability.
[0058] They can be used in flexible sensors, biomedical devices or sustainable materials, and are suitable for wearable electronics, wound dressings, tissue engineering, construction or furniture.
[0059] Specifically, PVA / Lig-Ag-20 hydrogels have broad applications in multiple fields due to their excellent mechanical properties, electrical conductivity, and biocompatibility. In the field of flexible sensors, hydrogels can be used to prepare strain or pressure sensors suitable for wearable electronic devices such as health monitoring bracelets or sports tracking devices. The preparation method involves cutting the hydrogel into 5mm×20mm×1mm strips, encapsulating them in a polydimethylsiloxane (PDMS) film, and connecting them to copper electrodes. Tests have shown that their response time to pressure changes of 0.1-10kPa is less than 0.1 seconds. In the field of biomedical devices, the antibacterial properties of the hydrogel (thanks to the AgNPs) and the biocompatibility of PVA make it suitable for use in wound dressings and tissue engineering scaffolds. Antibacterial tests (against Escherichia coli and Staphylococcus aureus) showed an inhibition rate of 95-99%, and wound healing experiments (in mouse models) showed a 20-30% reduction in healing time. In tissue engineering applications, the hydrogels serve as cell scaffolds to support the growth of fibroblasts, with cell survival rates exceeding 90%. In the field of sustainable materials, hydrogels leverage the recyclability of lignin and are suitable for use as building insulation or furniture fillings. Mechanical testing has shown that deformation is less than 5% under a pressure of 1-10 MPa, and weathering tests (1000 hours of UV irradiation) reveal a performance degradation of less than 10%. The hydrogels are simple to prepare, costing approximately 50-70% of traditional conductive hydrogels, making them suitable for industrial production and demonstrating significant commercial potential.
[0060] Table 1 Lignin molecular weight before and after pretreatment
[0061]
[0062] Table 2 Tensile strain values
[0063]
[0064] Table 3 Compressive stress of PVA / Lig-Ag-20 and pure PVA hydrogels under different strains
[0065]
[0066]
[0067] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a hydrogel based on nano-lignin, characterized in that: The following steps are involved: S1. Pretreating a cellulose biomass raw material containing more than 15% lignin using a choline chloride-lactic acid deep eutectic solvent to prepare nano-lignin particles; S2, mixing the nano-lignin particles with silver nitrate and sodium hydroxide to synthesize lignin-silver nanoparticles through redox reaction; S3, adding the lignin-silver nanoparticles to the polyvinyl alcohol solution and mixing to form a mixture; S4. The mixture is subjected to freeze-thaw cycles to induce physical cross-linking to form a nanocomposite hydrogel.
2. The method for preparing a hydrogel based on nano-lignin according to claim 1, characterized in that: In step S1, the choline chloride-lactic acid deep eutectic solvent pretreatment is carried out at 100-140° C. for 4-8 hours, and the obtained nano-lignin particles have a weight average molecular weight of 1400-1700 g / mol and a polydispersity coefficient of 1.2-1.
5.
3. The method for preparing a hydrogel based on nano-lignin according to claim 1, characterized in that: In step S2, the nano-lignin particles are dissolved in a sodium hydroxide solution with a pH of 9-11 at a concentration of 0.04-0.06 g·mL-1, and the silver nitrate concentration is 0.08-0.12 g·mL-1. The obtained lignin-silver nanoparticles have a particle size of 300-350 nm and a zeta potential of -25 to -35 mV.
4. The method for preparing a hydrogel based on nano-lignin according to claim 1, characterized in that: In step S3, the mass fraction of the polyvinyl alcohol solution is 8-12%, and it is prepared at 70-90°C. After the lignin-silver nanoparticles are added, they are stirred at 60-70°C for 0.5-1.5 hours. + The mass fraction is 15% to 25%.
5. The method for preparing a hydrogel based on nano-lignin according to claim 1, characterized in that: In step S4, the freeze-thaw cycle is performed 2-4 times, the freezing condition is -25 to -15°C for 4-8 hours, and the thawing condition is 20-30°C for 1-3 hours.
6. A nano-lignin-based hydrogel, used in the method for preparing a nano-lignin-based hydrogel according to any one of claims 1 to 5, characterized in that: Based on polyvinyl alcohol, containing lignin-silver nanoparticles, Ag + The mass fraction is 15% to 25%, and the specific surface area is 1.2-1.4m 2 ·g -1 , with a uniform porous network structure.
7. The nano-lignin-based hydrogel according to claim 6, characterized in that When Ag + When the mass fraction is 20%, the tensile strength is 0.7-0.9MPa, the elongation at break is 280-320%, the Young's modulus is 2.0-2.5kPa, and the toughness is 1.0-1.3MJ·m -3 .
8. The nano-lignin-based hydrogel according to claim 6, characterized in that The compressive stress at 60% strain is 200-250 kPa, and there is no obvious stress reduction after 80-120 compression cycles at 40% strain.
9. The nano-lignin-based hydrogel according to claim 6, characterized in that Pressure sensitivity is 2.5-2.7kPa -1 , the storage modulus and loss modulus are 8–12 times higher than those of pure PVA hydrogel in the frequency range of 0.01 to 10 Hz, exhibiting shear-thinning behavior.
10. The nano-lignin-based hydrogel according to claim 6, characterized in that They can be used in flexible sensors, biomedical devices or sustainable materials, and are suitable for wearable electronics, wound dressings, tissue engineering, construction or furniture.
Citation Information
Cited By
Lignin-derived carbon aerogel loaded metal nano-enzyme as well as synthesis method and application thereof
CN121695861A